Who invests in home equity to exempt wealth from bankruptcy? - Stefano Corradin; Reint E. Gropp; Harry Huizinga; Luc Laeven (European Central Bank (ECB), 2011)
Homestead exemptions to personal bankruptcy allow households to retain their home equity up to a limit determined at the state level. Households that may experience bankruptcy thus have an incentive to bias their portfolios towards home equity. Using US household data from the Survey of Income and Program Participation for the period 1996-2006, we find that especially households with low net worth maintain a larger share of their wealth as home equity if a larger homestead exemption applies. This home equity bias is also more pronounced if the household head is in poor health, increasing the chance of bankruptcy on account of unpaid medical bills. The bias is further stronger for households with mortgage finance, shorter house tenures, and younger household heads, which taken together reflect households that face more financial uncertainty.
Keywords: G11; K35; R21; 330; Home ownership; Homestead exemptions; Personal bankruptcy; portfolio allocation